1993
DOI: 10.1002/1097-0142(19930601)71:11<3472::aid-cncr2820711103>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic adenocarcinoma to the uterine cervix from gastric cancer. A clinicopathologic analysis of 16 cases

Abstract: Background. Metastatic adenocarcinoma to the uterine cervix from gastric cancer is rare, and the clinicopathologic features of this metastasis are unclear. Methods. A clinicopathologic review of 16 patients with metastatic adenocarcinoma to the uterine cervix from gastric cancer was performed. Results. The ages of the patients ranged from 29 to 57 years, and 81.3% of the patients were premenopausal. Nine of the patients had undergone gastrectomy previously. In 11 patients the histologic type of the gastric can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 21 publications
0
40
0
Order By: Relevance
“…Mucinous adenocarcinoma of the uterine cervix has subtypes: endocervical, intestinal, and signet-ring cell [4]. Signet-ring cell adenocarcinoma in the female genital tract most commonly involves the ovary and mostly presents a metastasis from the stomach [2]. In the literature, primary signet-ring cell carcinoma of cervix is extremely rare [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mucinous adenocarcinoma of the uterine cervix has subtypes: endocervical, intestinal, and signet-ring cell [4]. Signet-ring cell adenocarcinoma in the female genital tract most commonly involves the ovary and mostly presents a metastasis from the stomach [2]. In the literature, primary signet-ring cell carcinoma of cervix is extremely rare [5].…”
Section: Discussionmentioning
confidence: 99%
“…The current frequency of cervical adenocarcinoma is 15-20% of all cervical carcinomas and most of them are endocervical type [1]. Adenocarcinomas with signet ring cell are mostly metastatic from gastric, breast, colonic or ovarian carcinomas and primary tumor is extremely rare [2][3][4]. We describe an unusual case of woman with having primary signet ring cell carcinoma of the uterine cervix.…”
mentioning
confidence: 93%
“…In these cases, however, the patients could be asymptomatic, without uterine bleeding (28). Genital bleeding is also the most frequent symptom, followed by ascites and lower abdominal pain, in women with metastasis from gastric cancer to the uterine cervix (43). Rarely, metastasis to the uterine cervix from gastric cancer presents with ureteral obstruction (30,44), although it is extremely rare for these lesions to be found at the metastatic site mimicking advancedstage disease (International Federation of Gynecology and Obstetrics stage IIIB).…”
Section: Clinical Presentationsmentioning
confidence: 99%
“…Histologically, metastatic carcinoma to the uterine corpus is characterized by focal occurrence, lack of necrosis and the lack of accompanying premalignant changes in the endometrium (49). As regards metastatic adenocarcinoma to the uterine cervix from gastric cancer, Imachi et al (43) reviewed 16 patients and reported that 9/16 (56.3%) patients exhibited abnormal cytological findings. However, 8/14 (57.1%) of the patients showed no abnormal findings on colposcopy.…”
Section: Diagnosismentioning
confidence: 99%
“…Occasionally, metastases to other organs, such as the prostate gland [1], the gluteal muscle [2], or the cervix [3] are described. To our knowledge, this is the first report of the lymphogenic metastasis of a signet ring cell gastric carcinoma to an aortic aneurysm.…”
Section: Discussionmentioning
confidence: 99%